Analysis of Finansial Ratios Determinants on Altman Z-Score in Unicorn Companies in Indonesia 2020-2025 Period - Fadlian, Dicky (Dinasti Publisher, 2026)
Indonesia’s digital economic transformation has produced 14 unicorn companies with unique financial characteristics that prioritize exponential growth over short-term profitability. This study aims to analyze the influence of finansial rasio determinants on the Altman Z-Score of Indonesian unicorn companies for the 2020-2025 period. Using a quantitative approach with a comparative causal design, this study analyzed panel data from 9 unicorn companies with a total of 54 observations through a fixed effects regression model. The results show that all five finansial rasio components have a significant positive effect on the Althman Z-Score, with the EBIT to total assets ratios as the most dominant determinant (coefficient 3.234), followed by working capital to total assets (2.145), retainded earnings to total assets (1.876), sales to total assets (0,934), and market value of equity to total liabilities (0,567). Simultaneously, the five ratios explain 78.45 percent of the variation in the Z-Score with an F-statistic of 35.426. A temporal analysis identified an increase in the proportion of companies in the safe zone from 22.2 percent to 44,4 percent, indicating the financial resilience of th unicorn ecosystem post-pandemic. This research contributtes to the literature on bankruptcy prediction in emerging markets and provides a framework form evaluating health for stakeholders in making investment decisions in the digital economy.